A COMPARATIVE CLINICAL RETROSPECTIVE STUDY FOR EVALUATING THE DIETARY ETIOLOGICAL FACTORS CAUSES PURISHAJ KRIMI (Journal of Pharmaceutical Negative Results, 2023)
Background: In literature numerous dietary etiological factors causing Purishaj Krimi (Intestinal worms) are described. Present study aimed to validate textual dietary etiological factors as well as to enlighten present dietary etiological factors causing Purishaj Krimi by comparing in both Purshaj Krimi subjects and Non Purishaj Krimi subjectsMethods: Dietary etiological factors which causes Purishaj Krimi were reviewed in literature considered as important evaluation parameters for study. These parameters were evaluated in both Purishaj Krimi and Non Purishaj Krimi populations, based on their medical history and current investigational recordsResult: In the present study, literature review which claimed dietary etiological factors causing Purishaj Krimi were evaluated in the study population. Theses comparison of dietary etiological factors between Purishaj Krimi and Non Purishaj Krimi populations aided us to validate dietary etiological factorsConclusion: The clinical retrospective study validated actual dietary etiological factors causing Purishaj Krimi either by direct entry of Krimi in body or by providing suitable environment for Krimi production in the body.